2015
DOI: 10.1021/acs.inorgchem.5b00615
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Electrochemical and Catalytic Features of BIAN- and BIAO-Derived Ruthenium Complexes

Abstract: This article deals with a class of ruthenium-BIAN-derived complexes, [Ru(II)(tpm)(R-BIAN)Cl]ClO4 (tpm = tris(1-pyrazolyl)methane, R-BIAN = bis(arylimino)acenaphthene, R = 4-OMe ([1a]ClO4), 4-F ([1b]ClO4), 4-Cl ([1c]ClO4), 4-NO2 ([1d]ClO4)) and [Ru(II)(tpm)(OMe-BIAN)H2O](2+) ([3a](ClO4)2). The R-BIAN framework with R = H, however, leads to the selective formation of partially hydrolyzed BIAO ([N-(phenyl)imino]acenapthenone)-derived complex [Ru(II)(tpm)(BIAO)Cl]ClO4 ([2]ClO4). The redox-sensitive bond parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 123 publications
1
2
0
Order By: Relevance
“…Inspection of the FMO distributions for these complexes indicate that the first and second reduction events in all cases are ligand centred and delocalised across the bisimine N=C-C=N moiety, whereas the first oxidation event in all cases is metal centred, with the second and third oxidations delocalised across one of the arylsubstituents each. These observations are in good correlation to electrochemical, EPR and computational results of previously reported BIAN complexes of various transition metals [22,[68][69][70][71][72][73][74]. The redox behaviour of complexes 1a, 2d, 3a, 4a and 4c are discussed here as representative examples for comparative purposes.…”
Section: Electrochemical Behaviour and Molecular Orbital Calculationssupporting
confidence: 83%
“…Inspection of the FMO distributions for these complexes indicate that the first and second reduction events in all cases are ligand centred and delocalised across the bisimine N=C-C=N moiety, whereas the first oxidation event in all cases is metal centred, with the second and third oxidations delocalised across one of the arylsubstituents each. These observations are in good correlation to electrochemical, EPR and computational results of previously reported BIAN complexes of various transition metals [22,[68][69][70][71][72][73][74]. The redox behaviour of complexes 1a, 2d, 3a, 4a and 4c are discussed here as representative examples for comparative purposes.…”
Section: Electrochemical Behaviour and Molecular Orbital Calculationssupporting
confidence: 83%
“…Ruthenium-based epoxidation catalysts have received much attention because of the well-developed Ru chemistry and the easy access of various redox states of Ru complexes. In particular, Nishiyama et al reported the first use of [Ru­(pdc)­(tpy)] ( 1 ; H 2 pdc = 2,6-pyridyl dicarboxylic acid; tpy = 2,2′:6′,2″-terpyridine; Figure ) as an alkene-epoxidation catalyst in the presence of non-atom-economic oxidants such as PhI­(OAc) 2 , O 2 / t BuCHO, and t BuOOH . Later on, Beller and co-workers developed a series of catalysts of [Ru­(pdc)­(pybox)] (pybox = pyridine-bis­(oxazoline) ligands; complex 2 ; Figure ) that use hydrogen peroxide as the oxidant, with high activity and selectivity toward asymmetric epoxidation of alkenes. The anionic ligand pdc 2– is essential to suppress the decomposition of hydrogen peroxide and to improve the efficiency of the Ru-pdc/H 2 O 2 system toward alkene epoxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, the MIANs steric properties and redox activity are intermediate in this series, suggesting the formation of a new type of complexes with unpredictable reactivity [1,2]. MIANs are strong coordinating ligands [3][4][5][6] because each includes carbonyl and imine functional groups conjugated with the naphthalene fragment.…”
Section: Introductionmentioning
confidence: 90%
“…In turn, the MIAN complexes have been far less studied (Scheme 1). Thus, it was found that zinc(II) complexes with MIANs are precatalysts for the reaction of the formation of guanidine and urea derivatives [6]. Mn I -MIAN complexes exhibited unusually high sensitivity to visible light, even in the solid state, and rapidly release carbon monoxide (CO) upon illumination [20].…”
Section: Introductionmentioning
confidence: 99%